Wave propagation and focusing of soft X‐rays by spherical bent microchannel plates. (5th February 2021) - Mazuritskiy, M. I.; Lerer, A. M.; Marcelli, A.; Dabagov, S. B.; Coreno, M.; D'Elia, A.; Rezvani, S. J.
Abstract : The experimental results and theoretical approach presented here can be successfully applied to measure and to characterize transmission and focusing properties of different spherically bent microchannel plate devices having different radii of curvature for possible applications with synchrotron radiation. Abstract : Synchrotron radiation sources have been used to study the focusing properties and angular distribution of X‐ray radiation at the exit of spherically bent microchannel plates (MCPs). In this contribution it is shown how soft X‐ray radiation at energies up to 1.5 keV can be focused by spherically bent MCPs with curvature radii R of 30 mm and 50 mm. For these devices, a focus spot is detectable at a distance between the detector and the MCP of less than R /2, with a maximum focusing efficiency up to 23% of the flux illuminating the MCP. The soft X‐ray radiation collected at the exit of microchannels of spherically bent MCPs are analyzed in the framework of a wave approximation. A theoretical model for the wave propagation of radiation through MCPs has been successfully introduced to explain the experimental results. Experimental data and simulations of propagating radiation represent a clear confirmation of the wave channeling phenomenon for the radiation in spherically bent MCPs.